A Registry to regionalized treatment of Unstable Angina/Non-ST Elevation Myocardial Infarction - Otte J Rachman (Jurnal Kardiologi Indonesia, 2014)
multicentre Registry to access the current usage of antiplatelet therapy was conducted recently in Indonesia, that can be found in the current edition of this journal. 1 This was the only registry conducted in Indonesia and this was the only one that try to see the current compliance of the anti-platelet therapy in patients with Unstable Angina / Non-ST Elevation Myocardial Infarction not undergoing PCI procedure in Indonesia. This was very relevant since there is a surge of this diseases in the last decade and more cardiologist worked in the area and also there is more cath lab available to do invasive therapy. Such a facility should be used appropriately and efficiently as not to overburden the available resources both in time and economic aspect, especially in the era of BPJS (universal Health Coverage) which already use up much of these resources.The BPJS program is an ideal program which give treatment to the majority of people but since the resources is limited it is the duty of the government not to use it indiscriminately and as efficient as possible so it can be delivered to the right people according to its priority. As Indonesia is comprised of large area with thousands of Islands and many population that are devided of many subethnics that are different in many